Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Super Optical Padang - Novalinda , Rina; Suryanta, Dolly iman (CV. ITTC INDONESIA, 2022)
This Scientific Paper discusses the Effect of Service Quality on Customer Satisfaction at Super Optical Padang. This study aims to reveal; (1) knowing the description of service quality at Super Optical, (2) knowing customer satisfaction at Super Optical Padang, (3) knowing the relationship between service quality and customer satisfaction at Super Optical Padang. This research was conducted by distributing questionnaires to customers who came to Super Optical Padang. , then the data that has been collected through the questionnaire is discussed based on the theory proposed in the literature review, and the data is presented based on the answers from the respondents who came to Super Optical Padang. Respondent samples taken were 30 respondents consisting of 11 male respondents (36.67%) and 19 female respondents (63.33%). The results of this study indicate that the variables of Service Quality and Customer Satisfaction have a correlation value of 0.502, which means that the two variables have a fairly strong relationship. Service Quality has a significant influence on Customer Satisfaction. The conclusion obtained from this study is that the influence of service quality is quite strong on customer satisfaction. And there are several dimensions of service quality that must be improved again, this is to continue to improve customer satisfaction.